Guide to technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Appropriate technology sourcebook: a guide to practical books for village and small community technology by Ken Darrow and Mike Saxenian 1993 800pp ISBN 0 917704 17 7 Pbk price UKL19.95 published by Volunteers in Asia and distributed by IT Pub